ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN KOPI INSTAN - Fityan Mizfar; Aldon Sinaga (Universitas Sebelas Maret, 2015)
Coffee (Coffea sp), has an important role as a significant influence in live and livelihood of majority community as well as foreign exchange earner for state. It is known that coffee is one of flagship products in Indonesian commodities, noted that Indonesia is one of the world's largest coffee exporting nation. Instant coffee which is available at this time has been accepted by community which is caused by two factors.First, manufacturers build consumer perceptions that the products are kind of instant coffee beverage that offers practicality in its presentation, and not leaving a coarse powder or residue when drunk. Second, intelligence producers through advertising, where instant coffee is identical with urban culture, modern society, and people who are always busy with various kinds of work which spends time. The research goal was to identify the factors influencing consumer decision in buying instant coffee, especially coffee consumers on internet social networking users, by using Quota NonProbabilistic Sampling. The data analysis in this study used multiple regression analysis. The population was the entire of social networking users both personal and group. The results showed that the factors influencing consumer decisions in buying instant coffee were: sex (1.555), duration of activity or working hours (0.933), education (0.198), and information (0.928). Sex factor (1.555) was dominant to influence consumer decisions in buying instant coffee. This occurred because there was psychological aspect that could pose great effects. It is recommended for entrepreneurs in marketing products through television media to be more enhanced because most consumers find out information about coffee through the media. And for further researchers, it is expected to examine other factors that may affect consumers in making decision in buying instant coffee.